STRATEGI PENINGKATAN PRODUKTIVITAS MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR: STUDI PADA PT DYSTAR COLOURS INDONESIA - Hattu, Shendy; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study explores the role of Organizational Citizenship Behavior (OCB) in enhancing employee productivity at PT DyStar Colours Indonesia. Guided by a qualitative case study approach with descriptive analysis, the research focuses on five key OCB dimensions: altruism, conscientiousness, sportsmanship, courtesy, and civic virtue. The findings reveal that altruism and conscientiousness are the most dominant behaviors, contributing to stronger teamwork, operational efficiency, and product quality. Factors such as organizational culture, transformational leadership, and job satisfaction are identified as primary drivers of OCB, although the absence of a formal reward system remains a limitation. Partial implementation of Green Human Resource Management (GHRM) initiatives, including training and knowledge sharing, has further stimulated employees’ proactive behaviors and sustainability awareness. Overall, the study underscores that integrating OCB into human resource management policies—supported by GHRM practices—serves as a strategic catalyst for sustainable productivity and competitive advantage in the chemical manufacturing industry.